The Assistance of Chronic Disease Patients Through Screening and Counseling in Improving Medical Resilience at Nur Hayati RSU Garut - Sahroni, Roni; Inami, Moh.; Ulfa; Fatimah, Siti; Siregar, Fatahuddin Aziz (Proceedings of Annual Conference on Community Engagement, 2022)
This community service aim to improve medical resilience through screening and counseling services for chronically ill patients at RSU Nur Hayati Garut. There were 150 patients with chronic disease who participated in this assistance, stroke (21 patients or 14%), diabetes mellitus (30 patients or 20%), hypertension (33 patients or 22%), chronic kidney failure (15 or 10%), cancer (24 patients or 16%), and heart failure (27 patients or 18%). The result is at the level of resilience, 130 patients (87%) have very high resilience, and 20 patients (13%) have a high level of resilience. The resilience items selected by the most patients strongly agree, found in two characteristics, which are existential aloneness, 112 patients (75%), and meaningfulness characteristics, 120 patients (80%). The conclusion is community health-based community service activities with patient assistance through periodic screening and counseling media have significant impact on medical resilience in chronic disease patients who are undergoing therapy.